2007
DOI: 10.1002/j.2161-0045.2007.tb00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Style and Dysfunctional Career Thoughts: How Attachment Style Can Affect the Career Counseling Process

Abstract: Saunders, 1994a). Two hypotheses related to attachment style and dysfunctional career thoughts were tested with 46 adult immigrants (17 men, 29 women). Results show that both attachment anxiety and avoidance were significantly related to scores on the CTI; increased attachment avoidance also significantly correlated with decision-making confusion and external conflict. Implications of the relationship between attachment style and dysfunctional career thoughts for the career counseling process are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 43 publications
0
4
1
1
Order By: Relevance
“…On the other hand, the results yielded no support for the hypothesis that avoidant attachment negatively predicts CA. This conflicts both with the predictions of adult attachment theory and with existing findings that insecure attachment negatively predicts career exploration behaviors (Littman-Ovadia, 2008), career self-efficacy (Ecke, 2007), emotion regulation (Kafetsios et al, 2014), and coping with stress (Leiter et al, 2015). There are various feasible explanations for this finding.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…On the other hand, the results yielded no support for the hypothesis that avoidant attachment negatively predicts CA. This conflicts both with the predictions of adult attachment theory and with existing findings that insecure attachment negatively predicts career exploration behaviors (Littman-Ovadia, 2008), career self-efficacy (Ecke, 2007), emotion regulation (Kafetsios et al, 2014), and coping with stress (Leiter et al, 2015). There are various feasible explanations for this finding.…”
Section: Discussioncontrasting
confidence: 68%
“…In theory, insecurely attached individuals should engage in less exploratory behaviors since they do not experience a “secure base” to explore from (Ainsworth et al, 1978). In line with this theoretical view, studies across the globe have found that avoidant and anxious attachment styles both negatively predict career exploration behaviors (Littman-Ovadia, 2008) and career self-efficacy (Ecke, 2007). Those with high levels of insecure attachment are hence theoretically less likely to actively plan career developmental tasks and transitions.…”
Section: Adult Attachment Theorymentioning
confidence: 81%
See 1 more Smart Citation
“…To the extent that the student grew up in a family where open expression of feelings was not encouraged, they may have difficulty expressing their feelings to their counselor about career decision-making problems. In order for the counselor to effectively address dysfunctional career thoughts, the student must be willing to openly discuss career and personal issues (Ecke, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrated that adolescents with greater levels of peer attachment have greater levels of career exploration and commitment (Felsman & Bluestein, 1999). Secure attachment has been reported to be linked to lower career thought dysfunction (Ecke, 2007). Therefore, attachment with peers would influence CA because secure peer attachment promotes career explorations and commitment (Blustein et al, 1995).…”
Section: Peer Attachmentmentioning
confidence: 99%